Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.21203/rs.3.rs-645295/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Crystallization of Bosonic Quantum Hall States

Abstract: The dominance of interactions over kinetic energy lies at the heart of strongly correlated quantum matter, from fractional quantum Hall liquids, to atoms in optical lattices and twisted bilayer graphene. Crystalline phases often compete with correlated quantum liquids, and transitions between them occur when the energy cost of forming a density wave approaches zero. A prime example occurs for electrons in high magnetic fields, where the instability of quantum Hall liquids towards a Wigner crystal is heralded b… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…In conclusion, we have shown that rotating vortex lattices in scalar Bose-Einstein condensates have two exact Nambu-Goldstone zero modes in their quasiparticle excitation spectra. How do these gapless modes give way for gapped strongly correlated quantum fluids deep in the LLL [26,69,70]…”
Section: < L a T E X I T S H A 1 _ B A S E 6 4 = " W A V G 5 J C N 8 ...mentioning
confidence: 99%
“…In conclusion, we have shown that rotating vortex lattices in scalar Bose-Einstein condensates have two exact Nambu-Goldstone zero modes in their quasiparticle excitation spectra. How do these gapless modes give way for gapped strongly correlated quantum fluids deep in the LLL [26,69,70]…”
Section: < L a T E X I T S H A 1 _ B A S E 6 4 = " W A V G 5 J C N 8 ...mentioning
confidence: 99%